Changes in vascular density in resected tissue of 97 patients with mild malformation of cortical development, focal cortical dysplasia or TSC‐related cortical tubers. Issue 79 (23rd November 2019) - Veersema, Tim J.; de Neef, Andrew; van Scheppingen, Jackelien; Ferrier, Cyrille H.; van Eijsden, Pieter; Gosselaar, Peter H.; van Rijen, Peter C.; Spliet, Wim G.M.; Braun, Kees P.J.; Mühlebner, Angelika; Aronica, Eleonora
Abstract : Recent studies suggested a possible association between malformations of cortical development and microvascular density. In this study we aimed to further elucidate the relation between microvascular density and cortical developmental abnormalities in a cohort of 97 patients with epilepsy and histologically proven mild malformation of cortical development (mMCD), focal cortical dysplasia (FCD) or tuberous sclerosis complex (TSC). Surgical tissue samples were analyzed with quantitative measures of vessel density, T‐cell response, microglial activation and myelin content. Subsequently, the results were compared to an age‐ and localization matched control group. We observed an increase in microvasculature in white matter of TSC cortical tubers, which is linked to inflammatory response. No increase was seen in mMCD or FCD subtypes compared to controls. In mMCD/FCD and tubers, lesional cortex and white matter showed increased vascular density compared to perilesional tissues. Moreover, cortical vessel density increased with longer epilepsy duration and older age at surgery while in controls it decreased with age. Our findings suggest for that the increase in white matter vascular density might be pathology‐specific rather than a consequence of ongoing epileptic activity. Increased cortical vessel density with age and with longer epilepsy duration in mMCD/FCD's and tubers, however, could be a consequence of seizures.